2013
DOI: 10.1088/0031-9155/58/22/8063
|View full text |Cite
|
Sign up to set email alerts
|

Molecular imaging based on x-ray fluorescent high-Z tracers

Abstract: We propose a novel x-ray fluorescence imaging setup for the in vivo detection of high-Z tracer distributions. The main novel aspect is the use of an analyzer-based, energy-resolved detection method together with a radial, scatter reducing collimator. The aim of this work is to show the feasibility of this method by measuring the Bragg reflected K-fluorescence signal of an iodine solution sample in a proof of principle experiment and to estimate the potential of the complete imaging setup using a Monte Carlo si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…The practical experience of our team with measurements of reference targets and dosimetry meets the results of these studies, such that the simulation error of Geant4 lies within reasonable limits, e.g., below 6 to 10% [21,23,25]. Furthermore, several GEANT4 simulation studies showed that the sensitivity of XFI in human-sized objects increased in the past decade [13,14,27].…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…The practical experience of our team with measurements of reference targets and dosimetry meets the results of these studies, such that the simulation error of Geant4 lies within reasonable limits, e.g., below 6 to 10% [21,23,25]. Furthermore, several GEANT4 simulation studies showed that the sensitivity of XFI in human-sized objects increased in the past decade [13,14,27].…”
Section: Introductionsupporting
confidence: 57%
“…However, clinical in vivo applications of XFI like molecular imaging with clinically available imaging modalities were not developed to date. This is mainly because the biggest problem for scanning big areas in human-sized objects is the high background due to multiple Compton scattering, which prevents fluorescence signals from being detected at reasonable marker concentrations [12,13]. This can, however, be counteracted in several ways, namely the use of a polarized incident X-ray beam, collimation, and by increasing the total detector area [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…in ref. 30 or our own previous work 31 . The second constraint is realised by using a set of molybdenum leaves, radially arranged around the beam, such that detected photons can only arise from within the scanning beam volume, effectively excluding higher-order Compton photons.…”
Section: Resultsmentioning
confidence: 97%
“…The grid can be designed in a number of ways, either linear or crossed, or planar or focused, and with different interspace and septa (grid bars) materials. Although one design using Bragg crystals has been proposed for XRF tomography [9], the setup is complex and results in a large loss of signal.…”
mentioning
confidence: 99%